Answer:
Option: D is the correct answer.
D. The y intercept of g(x) is equal to 2 plus the y intercept of f(x).
Step-by-step explanation:
We know that the y-intercept of a function is the y-value of the point where the x-value is zero.
i.e. it is the value of the function where x=0.
The function f(x) is given by:
[tex]f(x)=4\times (1.02)^x[/tex]
Now, when x=0 we have:
[tex]f(0)=4\times (1.02)^0\\\\i.e.\\\\f(0)=4[/tex]
and after looking at the table of values of the function f(x) we observe that:
when x=0 g(x)=6.
This means that the y-intercept of function f(x) is : 4
and the y-intercept of the function g(x) is : 6
i.e. y-intercept of the function g(x) =2+y-intercept of function f(x)